Therapy for hilar cholangiocarcinoma - D. Yu. Frantsev; O. N. Sergeeva; B. I. Dolgushin (Сибирский онкологический журнал)
Purpose: to present different modalities of biliary decompression and specific antitumor treatment of hilar cholangiocarcinoma (Klatkin tumor). material and methods. The review was based on 318 publications available from Pubmed, Medline, Elibrary, etc. in the interval time between 19212018. results. Hilar cholangiocarcinoma is a rare hepatobiliary malignancy with dismal prognosis demonstrating slow periductal infiltrative growth, late metastasis and causing death mainly due to local complications. Percutaneous transhepatic biliary drainage (PTBD) is the optimal way of biliary decompression for malignant hilar strictures nowadays. PTBD is the safest, technically accessible technique with reproducible results. Transpapillary decompression in Klatskin tumor patients is technically feasible in 40 % of cases only. Biliary resection accompanied by major hepatectomy is considered the only curative modality to the date, but its results aren’t satisfactory a well as the majority of patients aren’t seemed the surgical candidates. Thus the locoregional technologies, i.e. radiation therapy, radiofrequency ablation and photodynamic therapy (PDT), are widely spread. PDT should be preferred over other local modalities due to safety, efficiency, possibility of reinterventions, technical and economic accessibility. conclusion. Modern approaches to the management of Klatskin tumor do not differ much from the those proposed by the first researchers in the middle of the xxth century and comes down to the biliary stricture dilatation and the sustenance of the normal bile passage as long as possible. However, despite the strategic stagnation, significant tactical successes were achieved thus allowing significant prolongation of survival in previously considered incurable patients.